DINAMIKA ORANG TUA DALAM PROSES PEMBELAJARAN DI SD INPRES MANTAWA B - Vadini, Ni Made Satya; Anta, I Made Nuhari; Narayanti, Putu Satya (STAH Dharma Sentana Sulawesi Tengah, 2024)
The purpose of this study was to determine the dynamics of parents in the learning process at SD Inpres Mantawa B. This study used a qualitative method, the primary data source was obtained from the fifth grade teacher and student guardians. The results of this study stated that the role of parents in the learning process during the COVID-19 pandemic for grade V students at SD Inpres Mantawa B consisted of providing study guidance and providing motivation for children's learning. Obstacles faced by parents in helping the learning process of fifth grade students at SD Inpres Mantawa B include internet networks, learning facility constraints, parents' busyness constraints, parents' limited knowledge constraints and constraints regarding the lack of references or student learning resources. Efforts made by parents in helping the learning process of fifth grade students at SD Inpres Mantawa B are providing learning facilities and checking children's learning assignments.